EFFECTIVENESS OF ZAKAT FUND DISTRIBUTION ON EMPOWERING MSMEs: STUDY ON MSME IN SUMUR DISTRICT - Najmudin, Najmudin; Najib, M. Ainun; Atiah, Isti Nuzulul (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2021)
This study aims to (1) determine the effect of zakat funds on the economic empowerment of MSMEs actors after the Sunda Strait Tsunami disaster. (2) to determine the effect of Business Development Service (BDS) on the economic empowerment of MSMEs actors after the Sunda Strait Tsunami disaster. (3) determine the effectiveness of zakat funds and Business Development Service (BDS) for the economic empowerment of MSMEs actors after the Sunda Strait Tsunami disaster. The method used in this research is quantitative method. All of the data in this study are primary data obtained by distributing questionnaires to 11 Sumur sub-district MSMEs who receive zakat funds and business development services (BDS) from the Harapan Dhuafa Amil Zakat Institute. The analysis technique used is multiple linear regression analysis. All data were tested using SPSS v.19 software. The results of this study indicate, (1) Zakat funds partially have a significant effect on the economic empowerment of MSMEs actors after the Sunda Strait Tsunami disaster, because the t value of the variable capital assistance is greater than the t table value (9,476> 1,894) and the significance value is smaller than the alpha value (0.000 <0.05). (2) Business Development Service (BDS) partially has a significant effect on the economic empowerment of MSMEs actors after the Sunda Strait Tsunami disaster, because because the t value of the BDS variable is greater than the t table value (10,086> 1,894) and the significance value is smaller than the alpha value. (0.000 <0.05). (3). Zakat funds and Business Development Service (BDS) for the economic empowerment of MSMEs actors after the Sunda Strait Tsunami disaster.